Analisis Tanggung Jawab Pidana dan Pandangan Hukum Islam terhadap Pelaksanaan Arisan Online - Yudi, Rizki Maulana; Fardiansyah, Ahmad Irzal; Tamza, Fristia Berdian (QIYAS: JURNAL HUKUM ISLAM DAN PERADILAN, 2025)
Abstracts: This study aims to analyze the form of criminal responsibility and from the Islamic Law perspective carried out by the perpetrators of online arisan organizers, as well as to examine the legal efforts that can be taken in handling the case. By using qualitative research methods, the following results were obtained: 1. Criminal Responsibility, namely if the online arisan organizer commits an act of embezzlement of participant funds, then criminal sanctions can be imposed in accordance with the provisions of Article 372 and Article 378 of the Criminal Code which regulates criminal acts of embezzlement and fraud. 2. Efforts to resolve disputes due to default can be carried out between the organizer and Lottery participants through communication on social media as regulated in Article 28 paragraph (1) of Law Number 19 of 2016 concerning ITE. 3. Islamic Law's View of  Lottery Online.Keywords: Criminal Responsibility, Online Arisan, Islamic Law.Abstrak : Penelitian ini memiliki tujuan untuk menganalisis bentuk tanggung jawab pidana maupun dari Pandangan Hukum Islam yang dilakukan oleh pelaku penyelenggara arisan online, serta mengkaji upaya hukum yang dapat ditempuh dalam penanganan kasus tersebut. Dengan menggunakan metode penelitian kualitatif, diperoleh hasil sebagai berikut: 1. Tanggung Jawab Pidana, yaitu apabila penyelenggara arisan online melakukan tindakan penggelapan terhadap dana peserta, maka dapat dikenai sanksi pidana sesuai dengan ketentuan Pasal 372 dan Pasal 378 KUHP yang mengatur tentang tindak pidana penggelapan dan penipuan. 2. Upaya Penyelesaian Sengketa akibat wanprestasi dapat dilakukan antara penyelenggara dan peserta arisan melalui komunikasi di media sosial sebagaimana diatur dalam Pasal 28 ayat (1) Undang-Undang Nomor 19 Tahun 2016 tentang ITE. 3. Pandangan Hukum Islam Terhadap Arisan Online.Kata kunci: Tanggung Jawab Pidana, Arisan Online, Hukum Islam.